Measuring Website Usability Construct as Second Order Construct in Website Usability Model - Nur Sukinah, Aziz; Adzhar, Kamaludin (American Scientific Publisher, 2018)
Usability is one of the important factors that determine the successfulness of a web site. There are many elements for website usability such as learnability, interface, efficiency and many more. Therefore, it makes the model of website usability become complex. This study analyzes the website usability as second order construct in the model. Most of the previous works list the website usability and the model for website usability in hierarchical model. This study identifies the major elements in website usability from the previous studies and usability standards. The study identified effectiveness, efficiency, learnability, navigation, content, interface design and accessibility as elements in the website usability. About 654 data from respondents are analyze using PLS-SEM approach. The result shows that model which is include website usability model as second order are significant to satisfaction and intention to use elements.